Environmental Neocolonialism and the Quest for Social Justice in Imbolo Mbue’s How Beautiful We Were - Gasztold, Brygida (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The article addresses the problems of environmental degradation, as illustrated and explored in Imbolo Mbue’s recent novel How Beautiful We Were (2021), which juxtaposes the fictional oil company Pexton’s corporate greed with the push for rapid economic growth in a less developed world. Intrusions into the fictional African country’s sovereignty are manifested by foreign capital’s extraction of its most valuable natural resource—oil—which results in environmental harm and the disruption of Indigenous, communal life. The novel critiques the hazardous methods of crude oil exploitation, which put human health and life at risk. It demonstrates how uneven distribution of oil’s benefits sanctions corruption and fosters economic injustice, while all attempts at restoring justice are thwarted as much by local as by foreign culprits. The novel’s defense of traditional ways and the critique of Western modernity and capitalism encourage the search for grounds on which alternate epistemologies could be built. At the intersection of Western dominance and Indigenous response, the novel explores how local groups mobilize the visions of the past to oppose extractive projects. As the novel’s nostalgic title signals the happy times now bygone, its multigenerational interest brings modernity into focus. Finally, I argue that the novel’s memories of colonial extractive practices not only highlight the importance of resource temporalities around resource extraction but also emphasize their impact on the future of local communities.